Determinants of post-penitentiary social reintegration: analysis of the needs and perceptions of persons released from detention in Romania - Chasciar, Denisa Ramona; Chasciar, Vasile; Coman, Claudiu; Toderici, Ovidiu Florin; Toader, Liviu; Kovacs, Attila; Bularca, Maria Cristina (Frontiers in Psychology, 2025)
IntroductionThe social reintegration of people released from prison represents a significant challenge in Romania, being influenced by factors such as discrimination, social marginalization, and economic difficulties.MethodsThis study analyzes the needs and perceptions of 1,039 people released from detention, using data collected through a questionnaire and an interview guide.ResultsThe results highlight the main difficulties encountered, including lack of community support (30.3%), difficulties in returning to family and community (17.8%), lack of housing (8.9%), and lack of financial resources (27.5%). The study also highlights the importance of professional qualification and access to the labor market, with 13.6% of respondents reporting a lack of adequate qualification and 22.8% experiencing difficulties due to a criminal record. The comparative analysis of these difficulties shows the need for multidimensional interventions and support from public and private institutions.DiscussionThe conclusions suggest the development of comprehensive public policies that address the complex needs of these individuals, including financial and housing support, vocational training programs, and anti-discrimination measures, to facilitate effective reintegration and reduce the rate of recidivism.